Acinetobacter baumannii NCIMB8209: A rare environmental strain displaying extensive insertion sequence-mediated genome remodeling resulting in the loss of exposed cell structures and defensive mechanisms - Repizo, Guillermo Daniel (2020)
Acinetobacter baumannii represents nowadays an important nosocomial pathogen of poorly defined reservoirs outside the clinical setting. Here, we conducted whole-genome sequencing analysis of the Acinetobacter sp. NCIMB8209 collection strain, isolated in 1943 from the aerobic degradation (retting) of desert guayule shrubs. Strain NCIMB8209 contained a 3.75-Mb chromosome and a plasmid of 134 kb. Phylogenetic analysis based on core genes indicated NCIMB8209 affiliation to A. baumannii, a result supported by the identification of a chromosomal blaOXA51-like gene. Seven genomic islands lacking antimicrobial resistance determinants, 5 regions encompassing phage-related genes, and notably, 93 insertion sequences (IS) were found in this genome. NCIMB8209 harbors most genes linked to persistence and virulence described in contemporary A. baumannii clinical strains, but many of the genes encoding components of surface structures are interrupted by IS. Moreover, defense genetic islands against biological aggressors such as type 6 secretion systems or CRISPR-cas are absent from this genome. These findings correlate with a low capacity of NCIMB8209 to form biofilm and pellicle, low motility on semisolid medium, and low virulence toward Galleria mellonella and Caenorhabditis elegans. Searching for catabolic genes and concomitant metabolic assays revealed the ability of NCIMB8209 to grow on a wide range of substances produced by plants, including aromatic acids and defense compounds against external aggressors. All the above features strongly suggest that NCIMB8209 has evolved specific adaptive features to a particular environmental niche. Moreover, they also revealed that the remarkable genetic plasticity identified in contemporary A. baumannii clinical strains represents an intrinsic characteristic of the species.